Fuzzy Logic based Control Strategies for Proton Exchange Membrane Fuel Cell System. Issue 1 (2022) - Mahali, Annada Prasad; Babu Gara, Uday Bhaskar; Mullapudi, Siva
Abstract: In this work, new fuzzy logic-based control strategies have been proposed to improve the performance of the non-linear Proton Exchange Membrane Fuel Cell (PEMFC) system. This paper considers the empirical approach to designing the controller. This allows the controller's design to be straightforward, and the controller can be fine-tuned as and when necessary. Three control strategies have been proposed in this paper, viz. Fuzzy feedforward control strategy (Strategy 1), Fuzzy feedforward controller with a feedback loop (Strategy 2), and Fuzzy feedforward controller with a feedback loop and conditional switch (Strategy 3) are proposed. The performance comparison of the proposed strategies is evaluated in terms of performance indicators such as the integral square error (ISE), integral absolute error (IAE), and total variation (TV) of the closed-loop control system. Furthermore, the proposed strategies keep the voltage at a given setpoint under load current variation. Finally, Strategy 3 is used to regulate the oxygen excess ratio (OER) at a reasonable value under load current variation to avoid oxygen starvation and keep the voltage at a defined point of a PEM fuel cell system. The results show that Strategy 3 provides better performance than other strategies